2020
DOI: 10.3892/ol.2020.11252
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of ovarian clear cell cancer compared with other epithelial cancer types: A population‑based analysis

Abstract: In order to compare the clinicopathological characteristics and survival outcomes of patients with ovarian clear cell carcinoma (CCC) to other epithelial cancer types, a total of 27,290 patients were analyzed, including 2,424 patients with CCC (8.9%), 3,505 patients with endometrioid cancer (EC) (12.8%), 2,379 patients with mucinous cancer (MC) (8.7%) and 18,982 patients with serous cancer (SC) (69.6%). Patients with EC had the most favorable prognosis and patients with SC had the poorest prognosis among all e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 26 publications
6
31
0
Order By: Relevance
“…121 Ovarian CCC has a poor prognosis of all the epithelial ovarian cancers. 122 Immunohistochemical analysis showed HNF1B nuclear staining in clear cell carcinoma specimens but minimal nuclear staining in non-clear cell carcinoma specimens. HNF1B may be an excellent CCC-specific molecular marker.…”
Section: Cancermentioning
confidence: 96%
“…121 Ovarian CCC has a poor prognosis of all the epithelial ovarian cancers. 122 Immunohistochemical analysis showed HNF1B nuclear staining in clear cell carcinoma specimens but minimal nuclear staining in non-clear cell carcinoma specimens. HNF1B may be an excellent CCC-specific molecular marker.…”
Section: Cancermentioning
confidence: 96%
“…30 This poorer outcome for patients with advanced-stage clear cell carcinoma has been confirmed in a study based on SEER data. 32 Recurrence of clear cell carcinoma tends to occur at multiple sites, and Hogan et al reported that 38 of 61 patients with recurrent clear cell carcinoma (62%) had multiple-site recurrence involving pelvic, extrapelvic, intrathoracic, lymph node and cerebral/meningeal sites. 33 The prognosis of patients with recurrent clear cell carcinoma is poorer than that of patients with recurrent serous carcinoma.…”
Section: Reviewmentioning
confidence: 99%
“…The conventional tumor marker CA125 has long been used in the diagnosis of HGSC. It is elevated in 75.6% of serous carcinoma cases but in only 57.6% of OCCC cases 91 . Thus, CA125 is a poor marker for OCCC, with only a mildly elevated baseline value and a frequent incidence of false-negative results 9 , 92 .…”
Section: Tumor Markersmentioning
confidence: 92%